Laboratory Evaluation of Temephos against Anopheles stephensi and Culex pipiens Larvae in Iran - Mohammad Reza Abai; Ahmad Ali Hanafi-Bojd; Hassan Vatandoost (Tehran University of Medical Sciences, 2016)
Background: Malaria is still a health problem in Iran. There are several vector control activities, including Indoor Residual spraying, using insecticide treated nets and larviciding including Temephos. In addition nuisance mosquitos are prevalent in the urban areas. So that evaluation of this species to larvicide will provide a clue for management of vector control activities. Methods: Two mosquito species were used in this study: Anopheles stephensi were collected from Kazeroun and Culex pipiens from Tehran, capital of Iran. All the tests were carried out according to the WHO method. All the test kis was provided by WHO. Results: Results showed a LC50= 0.0523 and LC90=0.3822 mg/l for An. stephensi. The figure for Cx. pipiens was 0.1838 and 0.8505 mg/l respectively. Conclusions: monitoring of insecticide resistance to Temephos should be evaluated regularly for management of vector control.